Value of Intraoperative Sonography in Pancreatic Surgery. (1st July 2015) - Weinstein, Stefanie; Morgan, Tara; Poder, Liina; Shin, Lewis; Jeffrey, R. Brooke; Aslam, Rizwan; Yee, Judy
Abstract : The utility of intraoperative sonography for pancreatic disease has been well described for detection and evaluation of neoplastic and inflammatory pancreatic disease. 1 – 8 Intraoperative sonography can help substantially reduce surgical time as well as decrease potential injury to tissues and major structures. Imaging with sonography literally at the point of care—the surgeon's scalpel—can precisely define the location of pancreatic lesions and their direct relationship with surrounding structures in real time during surgery. This article highlights our experience with intraoperative sonography at multiple institutional sites for both open and laparoscopic surgical procedures. We use intraoperative sonography for a wide range of pancreatic disease to provide accurate localization and staging of disease, provide guidance for enucleation of nonpalpable, nonvisible tumors, and in planning the most direct and least invasive surgical approach, avoiding injury to the pancreatic duct or other vital structures.